2006
DOI: 10.1111/j.1475-6773.2006.00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospice Enrollment and Evaluation of Its Causal Effect on Hospitalization of Dying Nursing Home Patients

Abstract: Objective. To examine the patient, nursing home (NH), hospice provider, and local market factors associated with the selection of the Medicare hospice benefit by eligible NH residents, and evaluate the causal effect of hospice on end-of-life hospitalization rates. Data Sources/Study Setting. Secondary data for 1995-1997 for NH residents. Study Design. This retrospective cohort study includes NH residents in five states (Kansa, Maine, New York, Ohio, South Dakota) who died in the years 1995-1997. Medicare claim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
127
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 44 publications
7
127
0
2
Order By: Relevance
“…As in other studies, 9,35 we found the presence of DNR and DNH orders to be associated with a much lower risk of a hospital death. Of interest, approximately three-fourths of SNF residents with and without hospice had DNR orders, whereas approximately 10% of each group had DNH orders (documented on the MDS).…”
Section: Dying In Us Nursing Homes With Advanced Dementiasupporting
confidence: 68%
See 4 more Smart Citations
“…As in other studies, 9,35 we found the presence of DNR and DNH orders to be associated with a much lower risk of a hospital death. Of interest, approximately three-fourths of SNF residents with and without hospice had DNR orders, whereas approximately 10% of each group had DNH orders (documented on the MDS).…”
Section: Dying In Us Nursing Homes With Advanced Dementiasupporting
confidence: 68%
“…8,9 To identify residents who died with advanced dementia a diagnosis of ''Alzheimer's'' or ''Dementia other than Alzheimer's'' had to be documented on the MDS closest to death or on any Medicare Part-A claim (i.e., home health, hospice, hospital, outpatient, or SNF claim) in the last 12 months of life. The International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) diagnosis codes we used to capture dementia have been used by others 24,25 (290.xx, 291.2, 292.82, 294.1x, 294.8, 331.0-331.2, and 332.83).…”
Section: Data and Study Populationmentioning
confidence: 99%
See 3 more Smart Citations